The Structure, Process, and Outcome of Mentorship on Survivor with Schizophrenia: A Case Study - Rozali Arsyad Kurniawan; Suryani Suryani; Taty Hernawaty; Lilibeth Al-Kofahy (Faculty of Nursing Universitas Padjadjaran, 2021)
The personal recovery paradigm in schizophrenia patients require a change of service. One of the changes that can be made to support the schizophrenia recovery process is a change in the concept of the relationship between patients and nurses. Nurse mentorship for schizophrenia patients is a new terminology of innovation in a supportive relationship between health workers and patients. At present, it is not known how the structure, process, and outcome of mentorship to schizophrenia survivors. This study aimed to explain how the structure, process, and outcome of mentoring nurses to schizophrenia survivors. This research is qualitative research using the case study method involving three cases of mentorship conducted in Banyumas Regional Hospital. A total of nine participants were involved in this study which consisted of three nurses as mentors, three schizophrenia survivors, and three caregivers. Data were collected by semi-structured interview techniques, observation, and document review. After in-depth analysis seven research themes were found. Participants’ perception about the structure of mentorship include the theme mentorship requires a variety of abilities of nurses and conditions of survivors who can participate in mentorship. While the mentorship process includes the theme requires patience in mentorship, giving guidance for the recovery of survivors, and facing the recurrence of survivors due to treatment factors. Participants revealed the outcome of mentorship in the theme mentors feel inner satisfaction, and survivors feel more enthusiastic about life. The results of this study provide the view that mentorship has the potential to be developed into quality nursing interventions to support the recovery process of schizophrenia survivors.